Mitä murteita suomessa onkaan? Murresanaston levikin kvantitatiivista analyysiä - Leino, Antti; Hyvönen, Saara; Salmenkivi, Marko (Virittäjä, 2006)
A quantitative analysis of the distribution of dialect words (englanti) 1/2006 (110) A Quantitative Analysis of the Distribution of Dialect Words Finnish dialects have traditionally been divided into eastern and western dialects, although a three-way division into eastern, western and northern dialects has sometimes also been proposed. In the established two-way division, the western dialects have been further divided into six main areas and the eastern dialects into two, and there has been considerable unanimity on the boundaries of these areas. This dialect division is based principally on phonological and morphological features. The writers had access to some 9,000 different maps showing the distribution of dialect words. These maps were drawn up as part of the project to compile a dictionary of Finnish dialects. The writers have analysed this data using various data analysis tools, and the results so far have been fairly consistent with the previous understanding of the situation. The most significant difference, however, is that the analysis has strongly supported the idea that a northern dialects region can be just as clearly distinguished as the division between eastern and western dialects. This northern region contains the Central and Northern Ostrobothnian and Northern Finnish dialects, all previously classed as western dialects, and also the Kainuu dialects, which are traditionally considered a sub-group of the Savo dialects. Areas and boundaries are not always the most informative way to illustrate the geographical variation in language, however. Instead, the extent of the differences between dialects can prove a rewarding area for study, and variation can be divided into separate, uncorrelated components. The writers present the most significant of these components, along with the traditional dialect maps. The writers note that their analysis is primarily based on lexical considerations, which may affect the results a little. They also had access to only certain alphabetical sections of the dictionary. Nevertheless, the results support the traditionally held views quite closely, and the differences in comparison with previous studies are visible mainly in areas where phonological and morphological features provide scope for alternative interpretations. Antti Leino Saara Hyvnen Marko Salmenkivi